Habit, sedimentation and institutions - Shaun Gallagher (Cogent Arts & Humanities)
In contrast to intellectualist and behaviorist conceptions of habit, recent enactivist discussions argue that habits reflect a type of contextualized intelligence. This enactive anti-intellectualist view is a close cousin to the pragmatist and phenomenological conceptions of habit as embedded in bodily modes of response and sedimented in modes of perception. The phenomenological concept of sedimentation, however, provides a way to understand how habits relate to social/cultural/institutional factors, not unlike Bourdieu’s concept of habitus (and in spite of Bourdieu’s criticism of Husserl). Despite some important differences between the phenomenological and enactive approaches to habit, I argue that the concept of sedimentation can enrich the enactive analysis, allowing for a dynamical understanding of the role played by social, cultural and institutional factors in habit formation, and the role played by habit in the formation of institutions.